miR-21, miR-155, miR-192, and miR-375 Deregulations Related to NF-kappaB Activation in Gastroduodenal Fluid–Induced Early Preneoplastic Lesions of Laryngeal Mucosa In Vivo() - Sasaki, Clarence T. (Neoplasia, 2016)
Gastroduodenal refluxate found in the upper aerodigestive tract is not clinically uncommon. We recently demonstrated the neoplastic potential of gastroduodenal fluids (GDF) on hypopharyngeal mucosa, via NF-κB, using in vitro and in vivo models. Here we will explore the in vivo effect of GDF on laryngeal mucosa (LM) to induce early preneoplastic lesions related to NF-κB activation, along with deregulation of specific microRNA (miRNA) markers previously linked to laryngeal cancer. We used histological, immunohistochemical, automated quantitative analysis and quantitative polymerase chain reaction to examine LM from 35 C57Bl/6J mice previously treated with topical GDF against corresponding controls (4 experimental and 3 control groups; 5 mice/group). Our analysis showed that GDF produced early preneoplastic lesions in treated LM related to NF-κB activation. LM treated by acid and bile combination demonstrated significantly higher expression of the analyzed cell proliferation markers (Ki67, CK14, ∆Np63), oncogenic p-STAT3, and changes of cell adhesion molecules (E-cadherin, ϐ-catenin) versus untreated LM or LM exposed to acid alone (P < .0005). Furthermore, acidic bile but not neutral bile appeared to accelerate the expression of “oncomirs” miR-21, miR-155, and miR-192 (acidic bile versus neutral bile, P < .0001), while reducing tumor suppressor miR-375 (acidic bile versus neutral bile, P = .0137), previously linked to NF-κB and laryngeal cancer. Finally, acidic bile induced reduction of miR-34a, miR-375, and miR-451a, exhibiting an inverse correlation with NF-κB activation. SIGNIFICANCE: Bile in combination with acid has a selective tumorigenic effect on LM, inducing deregulation of “oncomirs” and tumor suppressor miRNAs, produced by NF-κB activation with molecular and early histopathological alterations linked to neoplastic transformation. Systematic acid suppression may in part convey a protective role.